Silver vanadate quantum dot / hollow tubular carbon nitride composite photocatalyst as well as preparation method and application thereof

By anchoring the Ag2V4O11 quantum dots on the hollow tubular g-C3N4, a composite catalyst is constructed, which solves the problem of low binding efficiency of g-C3N4 and Ag2V4O11 quantum dots in the prior art, and achieves efficient photocatalytic degradation efficiency and tetracycline removal rate.

CN119746855APending Publication Date: 2025-04-04BEIHUA UNIV
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411972836.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-30
Publication Date
2025-04-04

AI Technical Summary

Technical Problem

There is no effective method in the prior art to combine g-C3N4 nanotubes with Ag2V4O11 quantum dots to improve the photocatalytic degradation efficiency of the catalyst.

Method used

Ag2V4O11 quantum dots were prepared by hydrothermal method, and in-situ deposition method without templates and additives were used to anchor them on hollow tubular g-C3N4 to construct a composite catalyst to increase the absorption of visible light and specific surface area, and reduce the recombination of photogenerated carriers.

Benefits of technology

The photocatalytic degradation efficiency of the catalyst is significantly improved, the removal rate of tetracycline is improved, and the catalyst has strong stability.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure HDA0005219818150000011
    Figure HDA0005219818150000011
  • Figure HDA0005219818150000012
    Figure HDA0005219818150000012
  • Figure HDA0005219818150000021
    Figure HDA0005219818150000021
Patent Text Reader

Abstract

The invention relates to a silver vanadate quantum dot / hollow tubular carbon nitride composite photocatalyst as well as a preparation method and application thereof. The catalyst is of a hollow tubular structure, quantum dots with the length of about 25 microns, the diameter of about 5 microns and the size of 3-10 nm are loaded on the surface of the hollow tube, no obvious porous structure exists on triazine tubular carbon nitride, the thickness is uniform, and the material surface is rough. The hollow tubular g-C3N4 is prepared through a simple hydrothermal and low-temperature calcination method, the Ag2V4O11 quantum dots are prepared through a simple hydrothermal method, and the Ag2V4O11 / TCN composite photocatalyst is prepared through an in-situ deposition method without a template and auxiliaries. The catalyst is used for removing tetracycline. And the precursor and the product are easy to synthesize, environment-friendly and green. By synthesizing the Ag2V4O11 / g-C3N4 composite photocatalytic material, the absorption and specific surface area of visible light can be increased, and the recombination of photon-generated carriers can be reduced, so that the photocatalytic degradation efficiency of the catalyst is effectively improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of composite material preparation, and particularly relates to a silver vanadate quantum dot / hollow tubular carbon nitride composite photocatalyst and a preparation method and application thereof. Background Art

[0002] Antibiotic pollution of water bodies has received increasing attention. Tetracycline (TC), as a class of broad-spectrum antibiotics produced by actinomycetes, is widely used in clinical prevention and treatment of humans and animals, but it is also one of the main sources of persistent organic pollutants. Due to its low cost and high antibacterial activity, it has been widely used in disease treatment and livestock growth promotion. However, due to its poor absorption and metabolism in animals and the inability to be effectively removed by conventional means in existing sewage treatment processes, it often leads to environmental accumulation. If not handled properly, it will cause damage to the aquatic environment. Therefore, it is crucial to find an efficient technology for removing tetracycline from water. In recent years, photocatalysis has received widespread attention for its advantages such as high efficiency, simplicity and environmental protection.

[0003] g-C3N4 nanotubes are one-dimensional nanostructures with large specific surface area, smooth carrier transport, and high light capture rate. Therefore, they have been widely used in the field of photocatalysis. Tubular g-C3N4 (TCN) has such fascinating photocatalytic potential, but it also has certain limitations, such as insufficient visible light absorption, photoinduced electron-hole (e-hole) - / h + ) have limited its practical application due to its fast recombination speed and poor reusability.

[0004] Silver and silver-based nanoparticles have photocatalytic capabilities. Ag-based oxides have unique hybrid valence bands (O 2p orbitals and Ag 3d orbitals) and generally have narrow band gaps (E g ≤3eV) and highly dispersed valence band (VB), which have good light absorption ability and high photohole mobility, respectively. The semiconductor surface is modified with silver (Ag) and silver-based nanoparticles, which can expand the light capture range of visible light to near-infrared light due to the surface plasmon resonance effect. Silver-based quantum dots are favored in various fields due to their unique optical properties. Ag2V4O 11 The unique hybrid valence bands of V2P, O1s, and Ag 3d orbitals in quantum dots exhibit narrow band gaps and highly dispersed valence bands. 11 Quantum dots can be used as co-catalysts to effectively enhance the separation and transfer of carriers, expand the utilization of visible light, and can be used to modify and sensitize semiconductor materials with wide bandgap. In addition, they exhibit excellent photosensitivity and can significantly improve the ability of materials to absorb visible light.

[0005] There is no better preparation method in the prior art to combine g-C3N4 nanotubes and Ag2V4O 11 The combination of quantum dots effectively improves the photocatalytic degradation efficiency of the catalyst. Summary of the invention

[0006] The purpose of the present invention is to provide a silver vanadate quantum dot / hollow tubular carbon nitride composite photocatalyst and its preparation method and application, and to prepare tubular g-C3N4 (TCN) by hydrothermal method and simple sintering method, so as to solve the problems of low specific surface area and low light absorption efficiency of traditional bulk carbon nitride. 11 Quantum dots are then synthesized by in-situ synthesis technology without template or auxiliary agent to form Ag2V4O 11 Quantum dots are anchored on TCN to construct a composite catalyst to increase the absorption of visible light and specific surface area, and the recombination of photogenerated carriers is reduced by constructing a heterojunction, thereby improving the photocatalytic degradation efficiency.

[0007] The technical solution of the present invention:

[0008] A silver vanadate quantum dot / hollow tubular carbon nitride composite photocatalyst, wherein the catalyst presents a hollow tubular structure, the hollow tube is about 25 μm long and 5 μm in diameter, quantum dots with a size of 3-10 nm are loaded on its surface, and the triazine tubular carbon nitride has no obvious pore structure, has a uniform thickness, and has a rough material surface.

[0009] A method for preparing a silver vanadate quantum dot / hollow tubular carbon nitride composite photocatalyst, preparing hollow tubular g-C3N4 by a simple hydrothermal and low-temperature calcination method, and preparing Ag2V4O by a simple hydrothermal method 11 Quantum dots and Ag2V4O prepared by in-situ deposition without template or additives 11 / TCN composite photocatalyst.

[0010] Beneficial effects of the present invention:

[0011] 1. From the preparation method, the precursor and the product are easy to synthesize, environmentally friendly and green. 11 / g-C3N4 composite photocatalytic material can increase the absorption of visible light and specific surface area, and reduce the recombination of photogenerated carriers, thereby effectively improving the photocatalytic degradation efficiency of the catalyst. BRIEF DESCRIPTION OF THE DRAWINGS

[0012] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings in the following description are only embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on the provided drawings without paying creative work.

[0013] Figure 1 g-C3N4, Ag2V4O 11 and 5% Ag2V4O 11 Photo of / g-C3N4 sample.

[0014] Figure 2 g-C3N4, Ag2V4O 11 and 5% Ag2V4O 11 / XRD pattern of g-C3N4.

[0015] Figure 3 (a) g-C3N4, 5% Ag2V4O 11 / g-C3N4 nitrogen adsorption and desorption diagram.

[0016] Figure 3 (b) g-C3N4, 5% Ag2V4O 11 / Pore size distribution diagram of g-C3N4.

[0017] Figure 4 g-C3N4, Ag2V4O 11 and 5% Ag2V4O 11 FT-IR pattern of / g-C3N4.

[0018] Figure 5 (a) is the SEM image of g-C3N4.

[0019] Figure 5 (b) 5% Ag2V4O 11 / SEM image of g-C3N4.

[0020] Figure 5 (c) 5% Ag2V4O 11 TEM image of / g-C3N4.

[0021] Figure 6 (a) is BCN, g-C3N4, Ag2V4O 11 and Ag2V4O with different mass ratios 11 / g-C3N4 degradation graph within 2h.

[0022] Figure 6 (b) BCN, g-C3N4, Ag2V4O11 and Ag2V4O with different mass ratios 11 / g-C3N4 corresponding to the pseudo-first-order reaction kinetics curve and degradation rate constant k.

[0023] Figure 6 (c) 5% Ag2V4O 11 / TCN semiconductor composites for photocatalytic degradation stability.

[0024] Figure 6 (d) TC at 5% Ag2V4O with different catalyst dosages 11 Degradation curve in / TCN system.

[0025] Figure 6 (e) TC at 5% Ag2V4O with different catalyst dosages 11 Pseudo-first-order reaction kinetic curve and degradation rate constant k in / TCN system.

[0026] Figure 6 (f) TC degradation of 5% Ag2V4O under different irradiation times 11 UV-visible absorption spectrum of 2.5 N·m2 / TCN.

[0027] Figure 7 g-C3N4, Ag2V4O 11 and 5% Ag2V4O 11 UV-visible diffuse reflectance spectrum of / g-C3N4.

[0028] Figure 8 g-C3N4, 5% Ag2V4O 11 PL pattern of / g-C3N4.

[0029] Fig. 9 g-C3N4, 5% Ag2V4O 11 / EIS diagram of g-C3N4.

[0030] Fig.10 g-C3N4, 5% Ag2V4O 11 Photocurrent diagram of / g-C3N4. DETAILED DESCRIPTION

[0031] In order to solve the problems in the background technology, a silver vanadate quantum dot / hollow tubular carbon nitride composite photocatalyst and its preparation method and application are specially invented. We prepared Ag2V4O by a simple hydrothermal method. 11 Quantum dots are sensitive to light and can increase the absorption range of light. 11Quantum dots are anchored on tubular g-C3N4 to construct a composite catalyst to solve the bottleneck problems of low visible light absorption and utilization efficiency and easy recombination of carriers in traditional catalysts.

[0032] A silver vanadate quantum dot / hollow tubular carbon nitride composite photocatalyst

[0033] The catalyst presents a hollow tubular structure with a length of about 25 μm and a diameter of about 5 μm. Quantum dots with a size of 3-10 nm are loaded on its surface. There is no obvious pore structure on the triazine tubular carbon nitride, and the thickness is uniform and the material surface is rough.

[0034] Preparation method of silver vanadate quantum dots / hollow tubular carbon nitride composite photocatalyst

[0035] The technical scheme of the present invention is to prepare hollow tubular g-C3N4 by a simple hydrothermal and low-temperature calcination method, and to prepare Ag2V4O by a simple hydrothermal method. 11 Quantum dots and Ag2V4O prepared by a template-free and agent-free in-situ deposition method 11 / TCN composite photocatalyst.

[0036] Example 1

[0037] Step 1: Preparation of hollow tubular g-C3N4 (TCN)

[0038] (1) Dissolve 8 g urea and 5 g melamine in 80 mL deionized water and stir continuously for 3 h.

[0039] (2) The mixed solution was transferred into a 100 mL stainless steel reactor and heated at 180 °C for 20 h.

[0040] (3) After natural cooling, the precursor was centrifuged and washed (deionized water and ethanol) to remove impurities, and then dried in a vacuum drying oven at 60°C.

[0041] (4) The obtained precursor was placed in a crucible, heated to 550°C in a muffle furnace at a rate of 2.5°C / min, and maintained at this temperature for 4 h. The obtained yellow sample TCN powder was obtained.

[0042] Step 2: Ag2V4O 11 Preparation

[0043] (1) Dissolve 1 mmol of NH4VO3 in 15 mL of deionized water under magnetic stirring.

[0044] (2) 1 mmol of AgNO3 was added to the NH4VO3 solution under vigorous stirring and stirred vigorously for 3 h. The solution was then transferred to a 20 mL stainless steel reactor with a filling degree of 75% and heated at 180°C for 20 h.

[0045] (3) After natural cooling, the product was centrifuged and washed (deionized water and ethanol were washed three times respectively) to remove impurities and filter out large particles, and then dried in a vacuum drying oven at 70°C.

[0046] Step 3: Ag2V4O 11 Preparation of TCN

[0047] (1) Add 0.2 g of TCN into 50 mL of anhydrous ethanol solution and stir well.

[0048] (2) 0.0051 mg of Ag2V4O 11 Add to anhydrous ethanol and stir evenly, then add Ag2V4O 11 The suspension was added to the g-C3N4 suspension, and then the suspension was stirred for 12 h and then centrifuged to obtain a solid powder.

[0049] (3) The sample was transferred to a vacuum drying oven at 70°C and dried to obtain the product.

[0050] Example 2

[0051] Step 3: Ag2V4O 11 Preparation of Ag2V4O / TCN 11 The dosage is 0.0105 mg, the dosage of TCN is 0.2 g, and the other steps are the same as in Example 1.

[0052] Example 3

[0053] Step 3: Ag2V4O 11 Preparation of Ag2V4O / TCN 11 The dosage is 0.0162 mg, the dosage of TCN is 0.2 g, and the other steps are the same as in Example 1.

[0054] Application of a silver vanadate quantum dot / hollow tubular carbon nitride composite photocatalyst

[0055] The catalyst of the present application is used for tetracycline removal, significantly improving the removal rate to 86.25%. After multiple cycle tests, the degradation rate of TC is still as high as 80%.

[0056] Specific methods for removing tetracycline:

[0057] The degradation of the samples was tested by photocatalytic degradation experiments of TC using an optical reactor (Porfilet PCX-50B multi-channel photocatalytic reaction system) under the irradiation of a 50W xenon lamp (λ>420nm) as a visible light source. First, 5-50mg of catalyst was added to 50mL of TC (20mg / L) solution and reacted in the dark for 30min to reach adsorption-desorption equilibrium. During this period, 4mL of the suspension was taken every 10min and centrifuged to obtain the supernatant. Then, a 2h photoreaction was performed, during which 4mL of the suspension was taken every 20min and centrifuged to obtain the supernatant of the photoreaction process. Finally, the concentration of TC in all supernatants was determined using a UV-visible spectrophotometer.

[0058] Photocatalytic degradation rate formula: D = (C0-C t ) / C0×100%,

[0059] Where: C0 is the initial concentration of TC, in mg / L. t It is the concentration of TC after time t, in mg / L.

[0060] For every 50 mL of 20 mg / L tetracycline solution, the amount of catalyst used is 5 mg, 10 mg, 20 mg, 30 mg, or 50 mg.

[0061] Detailed description with drawings

[0062] Figure 1 For the prepared samples g-C3N4, Ag2V4O 11 and 5% Ag2V4O 11 / g-C3N4, from which we can see that 5% Ag2V4O 11 / The density of g-C3N4 is smaller than that of g-C3N4.

[0063] Figure 2 For the prepared samples g-C3N4, Ag2V4O 11 and 5% Ag2V4O 11 / g-C3N4 XRD pattern. It can be seen from the XRD pattern that TCN has obvious characteristic peaks at 13.1° and 27.4°, corresponding to the (100) crystal plane and (002) crystal plane of hollow tubular carbon nitride, respectively. The diffraction peak at 27.4° is generated by the stacking of conjugated aromatic units, while the weaker characteristic peak at 13.1° is generated by the accumulation of in-plane structures. 11 The characteristic peaks of the sample at 23.2°, 29.1°, 29.6°, 30.4° and 50.9° correspond to its (002), (-203), (400), (111) and (120) crystal planes (PDF#49-0166). It is worth noting that 5% Ag2V4O11 / Ag2V4O was not found in TCN 11 The characteristic peaks of Ag2V4O 11 The actual load is small and highly dispersed.

[0064] Figure 3 (a) and (b) are g-C3N4 and 5% Ag2V4O 11 The pore size distribution curves and N2 adsorption-desorption isotherms of TCN and 5% Ag2V4O were used to study the N2 adsorption-desorption isotherms of g-C3N4. 11 The pore size distribution and specific surface area of ​​TCN are shown in Figure 2. Figure 3 (a) and (b) show. TCN and 5% Ag2V4O 11 The specific surface areas of TCN are 12.86 m 2 / g, 13.49m 2 / g. 5% Ag2V4O 11 / TCN exhibits a larger specific surface area than TCN, which is not only conducive to the transfer of photogenerated carriers, but also provides more active sites. In addition, its pore size distribution is within 1 to 10 nm.

[0065] Figure 4 For the prepared samples g-C3N4, Ag2V4O 11 and 5% Ag2V4O 11 FT-IR pattern of / g-C3N4. Figure 4 It shows that TCN is at 809cm -1 The obvious characteristic peak at 1640cm is due to the bending vibration of the CN bond, and the stretching vibration of the C=N bond is at 1640cm -1 The peaks appear at 1560, 1400 and 1310 cm-1, while the stretching vibrations of aromatic C=C bonds appear at 1560, 1400 and 1310 cm-1. -1 A peak appears at 1230cm -1 The peak at 3000-3500cm is due to the out-of-plane deformation of the CH bond. -1 The weak broad peaks between the two are attributed to the bending (OH) and stretching (OH) vibrations of adsorbed water molecules. 11 At 809cm -1 The peaks at 936, 774, and 503 cm are due to the stretching vibration of the bridged Ag-OV or possibly due to the OVO vibration; -1 The peaks at 1028, 936, 659, 646, and 627 cm-1 confirm the presence of symmetric and symmetric bridging stretching vibrations, which are due to the presence of VOV; -1 The band is caused by VO vibration. The broad spectrum of OH stretching ranges from 3300–3550 cm-1 , and at 1631cm -1 The peak at is due to OH bending, indicating the presence of physically absorbed water molecules. It is worth noting that at 5% Ag2V4O 11 Ag2V4O is almost invisible in the TCN sample. 11 The characteristic peaks are due to Ag2V4O 11 The content is relatively small and dispersed, which is consistent with the results of XRD.

[0066] Figure 5 (a) and (b) are the prepared samples g-C3N4 and 5% Ag2V4O 11 SEM image of / g-C3N4. Figure 5 It can be seen from (a) that the overall structure of the g-C3N4 sample is a hollow tube. Figure 5 (b) shows 5% Ag2V4O 11 / g-C3N4 composite material has a hollow tubular morphology; Figure 5 (c) 5% Ag2V4O 11 TEM image of / TCN, where we can clearly see the Ag2V4O 11 The quantum dots are attached to the tubular carbon nitride, and the diameter of the quantum dots is about 3-10nm. Proof 5% Ag2V4O 11 / g-C3N4 binary heterojunction photocatalyst was successfully synthesized.

[0067] Figure 6 (a) g-C3N4, Ag2V4O 11 and 5% Ag2V4O 11 / g-C3N4 photocatalytic degradation within 2 hours. It can be clearly seen that the composite sample has better degradation performance than the single sample, among which 5% Ag2V4O 11 / TCN has the best performance, with a TC degradation rate of 86.25% within 120 min. Under this condition, BCN, TCN, Ag2V4O 11 、2.5% Ag2V4O 11 / TCN, 7.5% Ag2V4O 11 The TC degradation rates of TCN and Ag2V4O were 67.13%, 74.12%, 67.52%, 78.60% and 81.73% respectively. 11 The combination of Ag2V4O can reduce the electron-hole collision and improve the transfer of photogenerated charges, thereby improving the photocatalytic activity. 11 The loading may have blocked some pores or covered the surface of TCN, reducing the active sites and thus the photocatalytic activity of the composite.11 、2.5%Ag2V4O 11 / TCN, 5% Ag2V4O 11 / TCN, 7.5% Ag2V4O 11 The degradation rate constants of the / TCN samples were 0.00906min -1 、0.01039min -1 、0.00913min -1 、0.01007min -1 、0.01336min -1 and 0.01144min -1 , of which 5% Ag2V4O 11 The degradation rate constant of / TCN is the largest, such as Figure 6 (b) as shown. Figure 6 (c) 5% Ag2V4O 11 UV-visible absorption spectrum of TC degradation in / TCN system, the absorption wavelength of TC is 359nm. It can be seen from the figure that in the dark reaction stage, 5% Ag2V4O 11 The absorbance of / TCN at 359nm remained basically unchanged, but the absorbance decreased significantly during the photoreaction stage, indicating that TC was effectively decomposed and removed during the degradation reaction. In order to test the stability of the composite material, four cycle experiments were carried out. The results are as follows Figure 6 As shown in (d), it can be seen that after 4 cycles of degradation, the degradation efficiency of TC can still reach 80%. 11 / TCN catalyst has strong stability. Figure 6 (d) shows the effect of different catalyst dosages on the degradation performance. It can be seen from the figure that with 5% Ag2V4O 11 When the amount of TCN catalyst increased from 5 mg to 50 mg, the degradation rate first increased and then decreased. When the amount of catalyst was 20 mg, the TC degradation rate was the largest (86.25%), and the degradation kinetic constant was 0.01336 min -1 Further increase in the amount of catalyst may cause agglomeration between catalysts, reduce active sites, and when the turbidity of the suspension increases, light scattering will occur in the solution, thereby reducing the light transmittance of the system and affecting the effective light absorption rate. At the same time, excessive addition of catalyst may also lead to competitive reactions, resulting in a decrease in the number of free radicals.

[0068] Figure 7 g-C3N4, Ag2V4O 11 and 5% Ag2V4O 11 UV-visible diffuse reflectance spectrum of the / g-C3N4 sample. It can be clearly seen that the 11After combination, 5% Ag2V4O 11 The absorption intensity of / TCN in the visible light range is higher than that of pure TCN, and the absorption edge is obviously shifted to the longer wavelength direction. 11 and TCN, 5% Ag2V4O 11 / TCN catalyst has better visible light driven photocatalytic performance and can produce more active substances, thus improving the degradation efficiency of TC. 5% Ag2V4O 11 / g-C3N4 has strong absorption in the ultraviolet region, and the absorption edge shows a red shift, corresponding to a band gap energy of 2.91eV. This shows that the construction of the heterojunction broadens the spectral response range and enhances the visible light absorption ability of the composite catalyst.

[0069] Figure 8 The prepared samples are g-C3N4, 5% Ag2V4O 11 PL diagram of / g-C3N4. Figure 8 It can be seen that compared with g-C3N4, 5% Ag2V4O 11 The PL peak intensity of g-C3N4 is significantly reduced. This is because under visible light irradiation, the photogenerated electrons are transferred from g-C3N4 to Ag2V4O 11 transfer, which improves the separation of photogenerated carriers and helps to improve the photocatalytic activity of the composite material.

[0070] Fig. 9 The prepared samples are g-C3N4, 5% Ag2V4O 11 EIS diagram of / g-C3N4. Fig. 9 As shown in Figure 2, in general, the impedance of the sample is determined by the arc radius. The smaller the radius, the faster the charge transfer and separation at the interface. Obviously, in both samples, 5% Ag2V4O 11 The radius of the / TCN nanocomposite is the smallest, indicating that the charge separation and transfer rate in the heterojunction is the fastest.

[0071] Fig.10 The prepared samples are g-C3N4, 5% Ag2V4O 11 / g-C3N4 photocurrent response diagram. Fig.10 It can be seen that TCN and 5% Ag2V4O 11 The photocurrent response of 5% Ag2V4O 11 / TCN has a higher photocurrent intensity. This shows that the constructed heterojunction effectively reduces the recombination of photogenerated carriers, thereby extending the lifetime of photogenerated electrons. This result is in good agreement with the fluorescence spectrum mentioned above. This result can also be further confirmed by EIS results.

[0072] The above schematically describes the present invention and its implementation methods, which are not restrictive. The drawings show only one implementation method of the present invention, and the actual structure is not limited thereto. Therefore, if a person skilled in the art is inspired by it and does not deviate from the technical solution of the present invention, and designs a structure and implementation similar to the technical solution based on the above implementation examples without creativity according to the technical essence of the present invention, they should all fall within the protection scope of the present invention.

Claims

1. A silver vanadate quantum dot / hollow tubular carbon nitride composite photocatalyst, characterized in that: The catalyst presents a hollow tubular structure with a length of about 25 μm and a diameter of about 5 μm. Quantum dots with a size of 3-10 nm are loaded on its surface. There is no obvious pore structure on the triazine tubular carbon nitride, and the thickness is uniform and the material surface is rough.

2. A method for preparing a silver vanadate quantum dot / hollow tubular carbon nitride composite photocatalyst, characterized in that: Hollow tubular g-C3N4 was prepared by a simple hydrothermal and low-temperature calcination method, and Ag2V4O was prepared by a simple hydrothermal method. 11 Quantum dots and Ag2V4O prepared by in-situ deposition without template or additives 11 / TCN composite photocatalyst.

3. The method for preparing a silver vanadate quantum dot / hollow tubular carbon nitride composite photocatalyst according to claim 2, characterized in that: Preparation of g-C3N4: First, urea and melamine were dissolved in deionized water, and magnetic stirring was continued for 3 hours. Then, the mixed solution was transferred to a stainless steel reactor and heated at 180°C for 20 hours. The filling degree was 80%. After natural cooling, the precursor obtained by the hydrothermal reaction was centrifuged and washed to remove impurities, and dried in a vacuum drying oven at 60°C. In order to further obtain hollow tubular g-C3N4, the obtained precursor was placed in an alumina crucible with a lid and heated to 550°C, and kept at this temperature for 4 hours to obtain a yellow sample g-C3N4 powder; Ag2V4O 11 Preparation: First, NH4VO3 was dissolved in deionized water under magnetic stirring; then AgNO3 was added to the NH4VO3 solution under vigorous stirring and stirred vigorously for 3 hours, and then transferred to a stainless steel reactor and heated at 180°C for 20 hours with a filling degree of 75%. After natural cooling, the precursor obtained by the hydrothermal reaction was centrifuged and washed to remove impurities and filter out large particles, and dried in a vacuum drying oven at 70°C; Ag2V4O 11 Preparation of g-C3N4: Add the prepared g-C3N4 into anhydrous ethanol solution and stir evenly. 11 Add to anhydrous ethanol and stir evenly, then add Ag2V4O 11 The suspension was added to the g-C3N4 suspension, and the mixed suspension was stirred for a period of time, and then centrifuged to obtain a solid powder, and finally the obtained solid powder was dried to obtain Ag2V4O 11 / g-C3N4 sample.

4. The method for preparing a silver vanadate quantum dot / hollow tubular carbon nitride composite photocatalyst according to claim 3, characterized in that: In the preparation step of the g-C3N4, the mass ratio of urea to melamine is 8:5, and the concentrations of NH4VO3 and AgNO3 are 1 mmol.

5. The method for preparing a silver vanadate quantum dot / hollow tubular carbon nitride composite photocatalyst according to claim 3, characterized in that: The g-C3N4 and Ag2V4O 11 The mass ratio is 200:(0.0051-0.0162mg).

6. The method for preparing a silver vanadate quantum dot / hollow tubular carbon nitride composite photocatalyst according to claim 3, characterized in that: The amount of g-C3N4 used is 0.2g, Ag2V4O 11 The dosage is 0.0051 mg, 0.0105 mg or 0.0162 mg respectively.

7. An Ag2V4O according to any one of claims 1 to 6 11 Application of / g-C3N4 composite photocatalyst in photocatalytic degradation of tetracycline.

8. Ag2V4O according to claim 7 11 / Application of g-C3N4 composite photocatalyst, characterized by: Specific method: Use an optical reactor (Porfilet PCX-50B multi-channel photocatalytic reaction system) to conduct a photocatalytic degradation experiment on TC under the irradiation of a 50W xenon lamp (λ>420nm) as a visible light source to test the degradation of the sample. First, add 5-50mg of catalyst to 50mL TC (20mg / L) solution and react in the dark for 30min to reach adsorption-desorption equilibrium. During this period, 4mL of the suspension was taken every 10min and centrifuged to obtain the supernatant. Then, a 2h photoreaction was carried out, during which 4mL of the suspension was taken every 20min and centrifuged to obtain the supernatant of the photoreaction process. Finally, the concentration of TC in all supernatants was determined using a UV-visible spectrophotometer. Photocatalytic degradation rate formula: D = (C0-C t ) / C0×100%, Where: C0 is the initial concentration of TC, in mg / L, C t It is the concentration of TC after time t, in mg / L.

9. Ag2V4O according to claim 8 11 / Application of g-C3N4 composite photocatalyst, characterized by: For every 50 mL of 20 mg / L tetracycline solution, the amount of catalyst used is 5 mg, 10 mg, 20 mg, 30 mg, or 50 mg.